Early to Middle Holocene subsistence strategies in the Pampas region: Evidence from the Arroyo Seco 2 site - Rafuse, Daniel Joseph (2017)
The following paper presents an analysis of the faunal material from the Arroyo Seco 2 site dated from the Early to Middle Holocene (ca. 8500 to 5800 14C yrs B.P.). The zooarchaeological and taphonomic data presented here provides significant information for understanding the dynamics of multiple occupations at the site, as well as the transition in prey choice for Pampean hunter-gatherers during this time period; from megamammals to large and finally medium sized prey. The Arroyo Seco 2 site contains four different fauna dated to Early and Middle Holocene, including Eutatus seguini, Lama guanicoe, Ozotoceros bezoarticus, and Rhea americana. The archaeological record from the Arroyo Seco 2 site shows that hunter-gatherers gradually shifted their generalist diet from extinct mega and large sized mammals during the Late Pleistocene to medium sized prey during the Early to Middle Holocene.